Intermediate conductance Ca2+-activated potassium channels are activated by functional coupling with stretch-activated nonselective cation channels in cricket myocytes - Numata, Tomohiro; Sato-Numata, Kaori; Yoshino, Masami (Frontiers in Insect Science, 2023)
Cooperative gating of localized ion channels ranges from fine-tuning excitation–contraction coupling in muscle cells to controlling pace-making activity in the heart. Membrane deformation resulting from muscle contraction activates stretch-activated (SA) cation channels. The subsequent Ca2+ influx activates spatially localized Ca2+-sensitive K+ channels to fine-tune spontaneous muscle contraction. To characterize endogenously expressed intermediate conductance Ca2+-activated potassium (IK) channels and assess the functional relevance of the extracellular Ca2+ source leading to IK channel activity, we performed patch-clamp techniques on cricket oviduct myocytes and recorded single-channel data. In this study, we first investigated the identification of IK channels that could be distinguished from endogenously expressed large-conductance Ca2+-activated potassium (BK) channels by adding extracellular Ba2+. The single-channel conductance of the IK channel was 62 pS, and its activity increased with increasing intracellular Ca2+ concentration but was not voltage-dependent. These results indicated that IK channels are endogenously expressed in cricket oviduct myocytes. Second, the Ca2+ influx pathway that activates the IK channel was investigated. The absence of extracellular Ca2+ or the presence of Gd3+ abolished the activity of IK channels. Finally, we investigated the proximity between SA and IK channels. The removal of extracellular Ca2+, administration of Ca2+ to the microscopic region in a pipette, and application of membrane stretching stimulation increased SA channel activity, followed by IK channel activity. Membrane stretch-induced SA and IK channel activity were positively correlated. However, the emergence of IK channel activity and its increase in response to membrane mechanical stretch was not observed without Ca2+ in the pipette. These results strongly suggest that IK channels are endogenously expressed in cricket oviduct myocytes and that IK channel activity is regulated by neighboring SA channel activity. In conclusion, functional coupling between SA and IK channels may underlie the molecular basis of spontaneous rhythmic contractions.